Transitioning of final year nursing students to professional nurses: A best practice guideline - van Rooyen, D.; Jordan, P.; Caka, E.M.; ten Ham-Baloyi, W. (South African Journal of Higher Education, 2020)
Abstract Background. The period of transition from student nurse to professional nurse in various healthcare contexts can be challenging. No best practice guideline could be found optimizing the transition of final year nursing students to professional nurses in the South African Military Health Service (SAMHS). Methods. A draft guideline was developed based on data from interviews with students and professional nurses, and an integrative literature review including guidelines on the transition of final year nursing students to professional nurses (content), using the AGREEII instrument (format), which was piloted using expert panel reviews. Results. The guideline covers four areas: support for new graduates, providing socialization and belonging, enhancing a positive clinical learning environment and ensuring retention of newly qualified professional nurses. Conclusion. The guideline provides a guide to best practices which can be used by nurse educators and managers but requires implementation to determine its impact on a successful transition period.